Effect of the carbon source on assessment of degrading bacteria with the spread-plating technique during in situ bioremediation - Damborský, J; Damborská, M; Stípek, S; Jesenská, A; Trantírek, L; Sklenár, V (Folia microbiologica, 2000)
Spread-plating belongs to traditional microbiological methods employed for quantification of subsurface microflora during bioremediation projects in the Czechia. Concentration of degrading organisms is estimated from the number of colonies grown on agar plates supplied with contaminant as the sole carbon source. The data obtained during in situ bioremediation of the Dacice site contaminated by cutting oil suggests that changes in the composition of the carbon source in the subsurface may cause a discrepancy between laboratory data and situation in subsurface.
Keywords: Environmental Microbiology; Carbon; Biodegradation, Environmental; biodegradace; Culture Media; oleje; Bacteriological Techniques; bakteriologické techniky; mikrobiologie životního prostředí; Bacteria; uhlík; Oils; kultivační média